Role of epicardial adipose tissue in the development of cardiovascular diseases - I. A. Mustafina; V. A. Ionin; A. A. Dolganov; V. Sh. Ishmetov; A. E. Pushkareva; T. A. Yagudin; K. V. Danilko; N Sh. Zagidullin (Российский кардиологический журнал)
Epicardial adipose tissue (EAT) has unique properties due to its special anatomical structure, thermoregulation, and metabolic activity. Dysregulated EAT provokes the synthesis of pro-inflammatory cytokines, disorders in the metabolism of fats and glucose, as well as contributes to fatty degeneration of the myocardium and heart failure development. EAT may serve as a risk factor and biomarker for cardiovascular diseases, and is also a potential therapeutic target. The purpose of this review was to highlight current research data on EAT, secreted adipokines, their effect on target tissue metabolism, and to systematize the relationship between EAT and cardiovascular diseases. In particular, its function, role in heart failure, atrial fibrillation, as well as the prognostic value of various microRNAs determined in EAT are highlighted.